FINANCIAL LITERACY TRANSFORMATION IN THE FINTECH ERA: A CASE STUDY OF E-WALLET USAGE AMONG GENERATION Z - Ragil retno palupi (Sekolah tinggi ilmu ekonomi pemuda, 2026)
ABSTRACT The rapid development of financial technology (fintech), particularly e-wallets, has shifted the economic transaction landscape of Generation Z from cash to digital. However, ease of access (inclusion) is often not accompanied by adequate financial management understanding. This study aims to analyze the transformation of financial literacy among Generation Z in the context of e-wallet usage and how this technology influences their financial behavior. This research employs a qualitative approach with a descriptive case study method. Data were collected through in-depth interviews with informants—university students who are active users of e-wallets (GoPay, OVO, ShopeePay, Dana) and observation of transaction behaviors. Findings indicate a shift in the perception of money's value into